The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1186/s41687-019-0118-1
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of the revised impact on family scale (RIOFS) in the hospital context

Abstract: Background The lack of formal instruments to measure Burden in primary caregivers of Children in a hospital context is limited because mostly of published instruments are related to cancer survivors, ambulatory environment or general context for children with chronic conditions, but none of them adapted property to prolonged hospitalization context. This leaves the rising population of hospitalized chronic children’s caregivers without a proper assessment. The aim of this study was to develop a ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The Impact on Family Scale (IFS) (Stein & Jessop, 2003) is a parent‐report questionnaire that evaluates the impact that caring for a child with a disability has on family life, and focuses on financial and familial‐social impact, personal strain and mastery. The revised 15‐item version (IFS‐15) has high internal consistency and excellent test–retest reliability as a single factor scale (Dehn et al, 2014; Jalil et al, 2019; Williams et al, 2006). Validity evaluations with parents of children with chronic illnesses (Williams et al, 2006) or epilepsy (Dehn et al, 2014) demonstrated moderate associations with factors such as severity of illness, child behaviour problems and parental restrictions due to daily care needs (Williams et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…The Impact on Family Scale (IFS) (Stein & Jessop, 2003) is a parent‐report questionnaire that evaluates the impact that caring for a child with a disability has on family life, and focuses on financial and familial‐social impact, personal strain and mastery. The revised 15‐item version (IFS‐15) has high internal consistency and excellent test–retest reliability as a single factor scale (Dehn et al, 2014; Jalil et al, 2019; Williams et al, 2006). Validity evaluations with parents of children with chronic illnesses (Williams et al, 2006) or epilepsy (Dehn et al, 2014) demonstrated moderate associations with factors such as severity of illness, child behaviour problems and parental restrictions due to daily care needs (Williams et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…However, the small sample size of the Montagnino study limits the interpretation of the findings. A revised version of the IOFS is available and has shown to be reliable in similar caregiver populations 33,34 . Replication studies using the instruments identified in this review in larger samples are needed.…”
Section: Discussionmentioning
confidence: 99%
“…A revised version of the IOFS is available and has shown to be reliable in similar caregiver populations. 33,34 Replication studies using the instruments identified in this review in larger samples are needed.…”
Section: Summary Of Evidencementioning
confidence: 99%
“…In studies carried out in other cultures, it has been documented that the Impact on Family Scale (IFS-PT) is a valid scale for assessing impact on the family when they experience a chronic pediatric illness in different contexts, and it may be used either in clinical settings or research settings [16,18,24,[49][50][51][52][53]. Regarding the cultural invariance of the IFS-PT, [15], using the 24-items version of IFS, we identified three factors (financial burden, familial/social impact, and personal strain) that were useful for cross-cultural comparisons between a U.S. and an Italian sample.…”
Section: Discussionmentioning
confidence: 99%
“…Stein and Jessop [18] suggested a reduction in the number of items in the original version to 15, which only covered the dimensions Family/Social Impact and Personal Strain, with a one-dimensional structure. This shorter version of the scale has been widely used [15,[19][20][21][22][23][24], and it was adapted in Portugal by Albuquerque et al [17]. Although the first results of this Portuguese adaptation support the unidimensional structure of the scale, they only pertain to parental burden in very specific contexts, such as the hospital, with parents being informed of the diagnosis of their child's disabilities, uropathies, and cardiopathies just before or after birth.…”
Section: Assessment Of the Impact Of Complex Chronic Illness On Familymentioning
confidence: 99%